2014
DOI: 10.5963/amsa0301004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal Heating on Double Diffusive Convection in a Couple Stress Fluid Saturated Anisotropic Porous Medium

Abstract: Abstract-The effect of internal heat source on double diffusive convection in a couple stress fluid saturated horizontal anisotropic porous layer was studied analytically by performing linear and nonlinear stability analyses. For linear stability analysis, normal mode technique was used, whereas for nonlinear stability analysis a minimal representation of Fourier series upto two terms was used. Effects of anisotropic parameter, couple stress parameter, solute Rayleigh number, Vadász number, Lewis number, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…The study observed that for downgrade throughflow, when the Peclet number is high, the effect of concentration based internal heat is significant. The effect of internal heat source on double diffusive convection in a couple stress fluid saturated horizontal anisotropic porous layer using linear and nonlinear stability analyses was studied in [12]. The results show that heat transport increased and mass transport decreased with increase in internal heat source parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The study observed that for downgrade throughflow, when the Peclet number is high, the effect of concentration based internal heat is significant. The effect of internal heat source on double diffusive convection in a couple stress fluid saturated horizontal anisotropic porous layer using linear and nonlinear stability analyses was studied in [12]. The results show that heat transport increased and mass transport decreased with increase in internal heat source parameter.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that when the internal heat parameter, increases, the critical Rayleigh number, will decreases. This will make the effect of source of the internal heat parameter destablize the start of stability convection, as verified by Srivastava et al, [12].…”
Section: Resultsmentioning
confidence: 78%
“…For Vadasz number, it is only valid for oscillatory state convection while stationary convection which remain the same during the Rayleigh number for the onset of convection occured at stable steady state, as verified by Srivastava et al, [12]. For this paper, stationary convection has been considered with couple stress fluid and internal heating effects in porous medium.…”
Section: Methodsmentioning
confidence: 85%
“…They plotted the streamlines, isotherms, and isohalines to represent the nature of convection. The effect of internal heating on double-diffusive convection in a couple stress fluid-saturated anisotropic porous medium was investigated by Srivastava et al [38]. The linear stability analysis was mode by a critical Rayleigh number for both stationary and oscillatory convection.…”
Section: Introductionmentioning
confidence: 99%